A modified microvascular "Tube-in-Tube" concept for penile construction in female-to-male transsexuals: Combined radial forearm free flap with anterolateral thigh flap. Issue 9 (September 2021) - Staud, Clement J.; Zaussinger, Maximilian; Duscher, Dominik; Radtke, Christine; Wenny, Raphael; Schmidt, Manfred; Huemer, Georg M.
Summary: Introduction: Phalloplasty is a complex surgical task and remains a significant challenge in plastic surgery. To date, there are various techniques; however, complication rates are still not satisfactory. Here, we present our surgical approach of a modified tube-in-tube concept combining a radial forearm free flap and an anterolateral thigh flap and assess its outcome in a series of female-to-male transsexuals. Patients and Methods: In this report, 21 female-to-male transsexual patients were included. The first surgical step includes colpectomy and elongation of the fixed part of the urethra with a full-thickness skin graft. Subsequently, a radial forearm free flap was adapted to build the inner tube which represents the neourethra. For the last step, a free anterolateral thigh flap is utilized as the outer tube of the neophallus. All patients were evaluated regarding aesthetic and functional outcomes as well as postoperative complications and revision surgeries. Results: Our results showed a 100% flap survival rate with a mean follow-up of 4.4 years (range, 2.7–6). Three radial forearm free flaps and one free anterolateral thigh flap presented with partial flap necrosis. Generally, complications occurred in 11 patients (52.4%). The most common complications were related to urethral reconstruction including fistula formation ( n = 8) and stenosis ( n = 5). All except one patient obtained the ability to void while standing. Conclusion: Despite the complexity, the initial results are very promising for a single-stage phalloplasty with complete functional creation of a neophallus. Further improvements have to be implemented for reduction of postoperative complications particularly regarding urethral reconstruction. Level of Evidence: IV (Therapeutic)